2014
DOI: 10.1111/tmi.12282
|View full text |Cite
|
Sign up to set email alerts
|

Changing epidemiology of maternal mortality in rural India: time to reset strategies for MDG‐5

Abstract: Abstractobjective To understand changes in epidemiology of maternal mortality in rural India in the context of increasing institutional deliveries and implementation of community-based interventions that can inform policies to reach MDG-5.methods This study is a secondary analysis of prospectively collected community-based data of every pregnancy and its outcomes from 2002 to 2011 in a rural, tribal area of Gujarat, India as part of safe-motherhood programme implemented by voluntary organisation, SEWA Rural. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 10 publications
3
27
0
Order By: Relevance
“…In rural areas with presumably less availability and/or access (transport) to care, more women die at home, which is similar to the findings of studies conducted in India, Tanzania and Zimbabwe . However, a recent study from Gujarat, India also reported that the majority of maternal deaths now occur in hospital …”
Section: Discussionsupporting
confidence: 80%
“…In rural areas with presumably less availability and/or access (transport) to care, more women die at home, which is similar to the findings of studies conducted in India, Tanzania and Zimbabwe . However, a recent study from Gujarat, India also reported that the majority of maternal deaths now occur in hospital …”
Section: Discussionsupporting
confidence: 80%
“…EP accounts for 3.5-7.1% of maternal mortality in India. 17,18 Maternal mortality in present study is 3.27%. More cases were seen between age group 21-30 years (54.8%) in present study which is similar to other studies conducted by Tuli AG et al, Spandana N et al 19,20 The most important cause of ectopic pregnancy is damage to the tubal mucosa may be due to infections, which could obstruct embryo transport due to scarring.…”
Section: Discussionmentioning
confidence: 46%
“…It accounts for 3.5-7.1% of maternal mortality in India. 11,12 In India the incidence of ectopic pregnancy reported by the Indian council of medical research (ICMR 1990) task force in their multi-centric case control study was 3.12 per 1000 pregnancies or 3.86 per 1000 live births in the hospital reported pregnancies. In present study the incidence is significantly higher at 3%, than most of the other studies in developing countries, where it ranges from 0.56-1.5%.…”
Section: Discussionmentioning
confidence: 99%